Creating Students’ Worksheet Using Canva in English Language Teaching (ELT) - Fitria, Tira Nur; Afdaleni, Afdaleni (Journal of Language, Literature and Teaching, 2024)
This descriptive qualitative research explores the integration of Canva in the creation of students’ worksheets for English Language Teaching (ELT). Canva, a versatile tool offering professional templates tailored for educational purposes, enhances the effectiveness of educational materials. The platform’s intuitive editing tools enable educators to customize templates with illustrations, icons, and graphics, thereby enriching visual appeal and engaging students effectively. Canva’s user-friendly interface facilitates quick printing or digital sharing of completed worksheets, optimizing time and resources in educational settings. By leveraging Canva, educators can create visually appealing and interactive worksheets that cater to diverse learning needs, thereby enhancing student engagement in language learning. In ELT, student worksheets serve specific purposes to develop various language skills. Vocabulary worksheets assist students in learning and retaining English vocabulary through activities like word matching and sentence creation. Grammar worksheets focus on understanding and applying grammar rules, involving exercises that identify parts of speech and transform sentences. Reading comprehension worksheets aim to improve comprehension of English texts by prompting students to identify details, decipher word meanings, infer author intentions, and make inferences. Writing practice worksheets provide opportunities for students to refine writing skills across genres such as letters, essays, narratives, and descriptions, fostering proficiency in outlining, paragraph development, and editing. Listening worksheets enhance auditory comprehension skills through tasks like listening to conversations or texts and responding to related questions or tasks. Speaking activities worksheets promote oral communication practice through dialogues, role-plays, or presentations, boosting students’ confidence in spoken English. Integrated skills worksheets combine reading, writing, listening, and speaking activities into cohesive exercises that allow students to apply language skills in meaningful contexts. In summary, these diverse types of worksheets support comprehensive language development and proficiency in English, addressing varied learning needs effectively within the ELT framework.